Survival of the flexible: hormonal growth control and adaptation in plant development - Wolters, Hanno; Jürgens, Gerd (Nature reviews. Genetics, 2009)
Key Points Indeterminate growth is a unique feature of plant development that is subject to intrinsic controls and modulated by environmental cues. Growth control is mediated by hormonal responses that rapidly alter gene expression programmes by inducing or preventing degradation of transcriptional regulators by the ubiquitin–proteasome system. Developmental targets of hormones are the meristems (stem cells and their transit amplifying daughter cells), lateral organ founder cells and the developing organ primordia. Plant development is modulated by the well-known classic hormones, such as auxin, cytokinin and gibberellin, and by newly identified growth regulators, such as peptides, strigolactone and fatty acid-related molecules. Numerous growth regulators are yet to be discovered. Hormones do not act in isolation but are interrelated by synergistic or antagonistic crosstalk so that the hormones modulate each other's biosynthesis or response. Hormones stimulate or terminate cell proliferation and thus regulate meristem or organ size, depending on the spatial distribution of their receptors and transcriptional regulators, as well as the relative concentrations of antagonistically acting hormones such as auxin and cytokinin. Environmental cues, such as light or stress, elicit stimulatory or inhibitory growth changes by altering local hormone biosynthesis or response. Despite tremendous recent progress, important aspects of hormone action in development are yet to be analysed, including hormone-regulated cell fate and tissue-specific hormone responses. Plant growth is controlled by both intrinsic and environmental signals and is mediated by hormonal signalling. Hormones are important for maintaining and regulating stem cell compartments in postembryonic plants, and current research is revealing many interactions between different hormone pathways. Plant development is subject to hormonal growth control and adapts to environmental cues such as light or stress. Recently, significant progress has been made in elucidating hormone synthesis, signalling and degradation pathways, and in resolving spatial and temporal aspects of hormone responses. Here we review how hormones control maintenance of stem cell systems, influence developmental transitions of stem cell daughters and define developmental compartments in Arabidopsis thaliana . We also discuss how environmental cues change plant growth by modulating hormone levels and response. Future analysis of hormone crosstalk and of hormone action at both single cell and organ levels will substantially improve our understanding of how plant development adapts to changes in intrinsic and environmental conditions.